Adulticide Resistance Status of Aedes albopictus (Diptera: Culicidae) in Sabah, Malaysia: A Statewide Assessment. Issue 6 (10th July 2019) - Elia-Amira, N M R; Chen, C D; Low, V L; Lau, K W; Haziqah-Rashid, A; Amelia-Yap, Z H; Lee, H L; Sofian-Azirun, M
Abstract: Resistance status of Aedes albopictus (Diptera: Culicidae) collected from Sabah, East Malaysia, was evaluated against four major classes of adulticides, namely pyrethroid, carbamate, organochlorine, and organophosphate. Adult bioassays conforming to WHO standard protocols were conducted to assess knockdown and mortality rates of Ae. albopictus . Among tested pyrethroid adulticides, only cyfluthrin, lambda-cyaholthrin, and deltamethrin were able to inflict total knockdown. The other adulticide classes mostly failed to cause any knockdown; the highest knockdown rate was only 18.33% for propoxur. With regards to mortality rate, Ae. albopictus was unanimously susceptible toward all pyrethroids, dieldrin, and malathion, but exhibited resistance toward bendiocarb, propoxur, dichlorodiphenyltrichloroethane, and fenitrothion. Additionally, correlation analysis demonstrated cross-resistance between bendiocarb and propoxur, and malathion and propoxur. In conclusion, this study has disclosed that pyrethroids are still generally effective for Aedes control in Sabah, Malaysia. The susceptibility status of Ae. albopictus against pyrethroids in descending order was cyfluthrin > lambda-cyhalothrin > deltamethrin > etofenprox > permethrin.